Application of Social Cognitive Theory in Promoting Tertiary Prevention Behavior among Hypertensive Patients in Tulungagung, East Java, Indonesia - Anggie Rahmatul Azizah; Ratih Puspita Febrinasari; Bhisma Murti; Okid Parama Astirin; Argyo Demartoto (Journal of Health Promotion and Behavior, 2025)
Background: Hypertension is a non-communicable disease that can affect individuals across all age groups, including the productive age population, largely due to changes in lifestyle. The implementation of tertiary prevention behaviors is essential to prevent disease complications such as coronary heart disease, stroke, kidney failure, and liver disease. This study aimed to analyze the application of Social Cognitive Theory in relation to tertiary prevention behaviors among patients with hypertension. Subjects and Method: This analytic observational study employed a cross-sectional design. The study subjects were patients with hypertension of productive age (15–64 years) in Tulungagung Regency, selected using a non-proportional random sampling technique, with a total sample of 220 participants. Data were collected using a research questionnaire that had been tested for validity and reliability. Multivariate data analysis was conducted using path analysis to examine both direct and indirect effects among variables. Results: There were direct and statistically significant effects of observational learning (b = 0.13; 95% CI = 0.01 to 0.24; p = 0.028), self-efficacy (b = 0.20; 95% CI = 0.05 to 0.35; p = 0.008), and attitude (b = 0.31; 95% CI= 0.17 to 0.45; p < 0.001) on tertiary prevention behaviors. Education was not significantly associated with tertiary prevention behaviors. Age (b = 0.17; 95% CI= 0.05 to 0.29; p = 0.005) and tertiary prevention behaviors (b= −0.38; 95% CI = −0.49 to −0.27; p < 0.001) showed direct and significant effects on blood pressure. Sex was not significantly associated with blood pressure. Social support, outcome expectations, and age had indirect effects on tertiary prevention behaviors through self-efficacy. Conclusion: There are direct effects of observational learning, attitude, and self-efficacy on tertiary prevention behaviors, as well as indirect effects of social support, outcome expectations, age, and education on tertiary prevention behaviors. In addition, age, sex, and tertiary prevention behaviors have direct effects on blood pressure.